Yksilöllisen liikuntaneuvonnan vaikutukset kehon koostumukseen ja liikunnan määrään - Plosila, Ella (2025)
Plosila, E. 2025. Effects of individualized physical activity counseling on body composition and physical activity levels. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in Exercise Medicine, 55 pp.